A survey among Korea Medicine doctors (KMDs) in Korea on patterns of integrative Korean Medicine practice for lumbar intervertebral disc displacement: Preliminary research for clinical practice guidelines. Issue 1 (December 2015) - Shin, Ye-sle; Shin, Joon-Shik; Lee, Jinho; Lee, Yoon; Kim, Me-riong; Ahn, Yong-jun; Park, Ki; Shin, Byung-Cheul; Lee, Myeong; Kim, Joo-Hee; Cho, Jae-Heung; Ha, In-Hyuk
Abstract Background Patients seek Korean Medicine (KM) treatment for a broad range of complaints in Korea, but predominantly for musculoskeletal disorders. We investigated lumbar Intervertebral Disc Displacement (IDD) practice patterns of Korean Medicine doctors (KMDs) within a hospital/clinic network specializing in KM treatment of spinal disorders through survey of diagnosis and treatment methods. Methods Questionnaires on clinical practice patterns of KM treatment for lumbar IDD were distributed to 149 KMDs on January 25th, 2015. The questionnaire included items on sociodemographic characteristics, clinical practice patterns, and preferred method of lumbar IDD diagnosis and treatment. KMDs were asked to grade each treatment method for absolute and relative importance in treatment and prognosis, and safety. Results A total 79.19 % KMDs (n  = 118/149) completed the survey, and results showed that integrative care mainly consisting of acupuncture, herbal medicine, Chuna manipulation, and pharmacopuncture was administered to IDD patients. The participant KMDs largely relied on radiological findings (MRI and X-ray) for diagnosis. 'Eight principle pattern identification', 'Qi and Blood syndrome differentiation' and 'Meridian system syndrome differentiation' theories were generally used for KM syndrome differentiation. The most frequently prescribed herbal medication was Chungpa-jun, and most commonly used Chuna technique was 'sidelying lumbar extension displacement treatment'. IDD patients received 1.9 ± 0.3 treatment sessions/week, and KMDs estimated that an average 9.6 ± 3.5 weeks were needed for 80 % pain relief. Conclusions This is the first study to investigate expert opinion on KM treatment of IDD. Further randomized controlled trials and clinical guidelines based on clinical practice patterns of KM are called for.